(untitled) (Journal of Health Sciences, 2014)
Introduction: Sick building syndrome (SBS) is a medical condition in which people in a certain buildings suffer from symptoms of illness or feeling unwell. The aim of this study was to determine the frequency of exposure of the employees of public institutions from the city of Osijek to harmful psychosocial factors of the working environment, to assess whether there is a connection between the exposure to these factors and the incidence of SBS symptoms and to clarify the nature of this connection.Methods: This cross-sectional study was conducted during May 2013 among 178 employees of public institutions in the city of Osijek. An anonymous questionnaire which contained questions relating to demographic data and working status of the participants, their exposure to various harmful psychosocial factors of the working environment and occurrence of certain symptoms of SBS among them was used as a research tool.Results: 96.1 % (171/178) of participants were exposed to harmful psychosocial factors of the working environment. Employees exposed to those factors more frequently expressed symptoms of SBS. The incidence and the number of symptoms of SBS among employees simultaneously grew with the increase of the number of harmful psychosocial factors of the working environment to which they were exposed.Conclusion: The study showed positive connection between the exposure to harmful psychosocial factors of the working environment and the incidence of SBS symptoms, highlighting this issue as a very important subject in the field of occupational medicine and health protection in the workplace.